Enhancing engineering students’ satisfaction with online learning: factors, framework, and strategies - Al-Khatib, Maryam; Alkhatib, Amira; Talhami, Mohammed; Kashem, Abdurahman Hafez Mohammed; Ayari, Mohamed Arselene; Choe, Pilsung (Frontiers in Education, 2024)
Introduction The learning experience has undergone significant changes recently, particularly with the adoption of advanced technology and online lectures to address challenges such as pandemics. In fields like engineering, where hands-on classes are essential, the online learning environment plays a crucial role in shaping students’ experiences and satisfaction. Methods This study aimed to explore the key factors affecting engineering students’ satisfaction with online learning. A structured survey was administered to 263 students across various engineering disciplines and academic levels, all of whom had experienced both in-person learning before the pandemic and online learning during the pandemic. Factor analysis and multiple linear regression were employed to analyze the data. Results The analysis identified interactions, services, and technology as the main factors positively influencing online learning satisfaction. The regression analysis further revealed that students’ satisfaction is significantly dependent on the availability and quality of online learning services, assessment and interaction tools, and technology. Discussion This study highlights the critical factors that enhance engineering students’ satisfaction with online learning. It offers strategies for educators to improve online learning environments, emphasizing the importance of quality services, assessment, and interaction tools. These findings can guide the development of more effective online learning experiences in engineering education.